Reduced Theta Inter‐Trial Phase Coherence in Error Processing: A Marker of Neural Dysfunction in Attention Deficit Hyperactivity Disorder - Devor, Tali; Einziger, Tzlil; Ben‐Shachar, Mattan S.; Klein, Christoph; Auerbach, Judith G.; Berger, Andrea (Psychophysiology, 2025)
ABSTRACT Cognitive control deficits and increased intra‐subject variability have been well established as core characteristics of attention deficit hyperactivity disorder (ADHD), and there is a growing interest in their expression at the neural level. We aimed to study neural variability in ADHD, as reflected in theta inter‐trial phase coherence (ITC) during error processing, a process that involves cognitive control. We examined both traditional event‐related potential (ERP) measures of error processing (i.e., error‐related negativity [ERN] and error‐positivity [Pe]) and theta ITC within a prospective longitudinal study of children at familial risk for ADHD. The participants were 63 male adolescents who were followed since birth. At the age of 17 years old, they performed the stop‐signal task (SST) while an electroencephalogram (EEG) recording was continuously carried out. The EEG data from the trials in which the subjects failed to inhibit their response were used to calculate three different neurophysiological measures (i.e., ERN, Pe, and theta ITC). Consistent with our hypotheses, theta ITC during error processing predicted ADHD symptomatology above and beyond the traditional ERP measures. Moreover, we found that ADHD symptoms throughout childhood were uniquely associated with theta ITC, beyond ADHD symptomatology during adolescence. Overall, our findings strengthen the view of increased neural variability (as reflected by theta ITC) as a neurophysiological characteristic of a core neural dysfunction in ADHD. Our study sheds new light on the significance of theta inter‐trial phase coherence (ITC) as a neurophysiological marker of a core neural dysfunction in ADHD. Our findings suggest that variability in the temporal dynamics of phase synchronization at theta frequencies may underlie the impaired implementation of cognitive control during error processing. Moreover, this neural deficit appears to be related to ADHD symptomatology observed in early childhood.